A critical appraisal of the Milan system for reporting salivary gland cytology (MSRSGC) with histological correlation over a 3‐year period: Indian scenario. Issue 5 (12th November 2018) - Pujani, Mukta; Chauhan, Varsha; Agarwal, Charu; Raychaudhuri, Sujata; Singh, Kanika
Abstract : Background: Fine needle aspiration cytology (FNAC) is the first line investigation for pre‐operative diagnosis of salivary gland lesions, but due to its inherent limitations remains a challenge for the cytopathologists. The recently proposed international risk stratification scheme, the Milan System for Reporting Salivary Gland Cytology (MSRSGC) aims to promote and standardise the communication between cytopathologist and clinician thereby improving patient care. Methods: A retrospective study of all salivary gland cytology cases was performed over a 3‐year period, reviewed by pathologists and categorised into 1 of the 6 diagnostic categories according to MSRSGC, namely, non‐diagnostic, non‐neoplastic, atypia of undetermined significance (AUS), benign neoplasm, and salivary gland neoplasm of undetermined significance (SUMP), suspicious for malignancy (SFM), and malignant neoplasm. Cyto‐ histological correlation was done wherever possible. Risk of malignancy (ROM) was calculated for each diagnostic category. Results: Out of a total of 150 salivary FNAC cases, histopathology was available for 64 cases. The sensitivity of FNAC was 81.8%, specificity was 100% while the diagnostic accuracy was 96.9%. The positive and negative predictive values were 100% and 96.4% respectively. The ROM for non‐diagnostic, non‐neoplastic, AUS, benign neoplasm, SUMP, SFM, and malignant categories were 0%, 10%, 50%, 2.5%, 50%, 100%, and 100% respectively. Conclusion: MSRSGC fulfils the critical need for a uniform, internationally acceptable reporting system with ROM specified for each category. However, large scale multi centre studies need to be conducted before its reliability and validity is proven.